2013
DOI: 10.3174/ajnr.a3600
|View full text |Cite
|
Sign up to set email alerts
|

Automated Quantitation of the Posterior Scleral Flattening and Optic Nerve Protrusion by MRI in Idiopathic Intracranial Hypertension

Abstract: BACKGROUND AND PURPOSE:Subjective determination of the posterior sclera flattening and optic nerve protrusion in MRI is challenging because of the 3D nature of the globe morphology. This study aims to develop and compare quantitative measures of globe flattening and optic nerve protrusion with subjective rating, and assess relationships with papilledema grade and intraocular and CSF pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
4
13
0
Order By: Relevance
“…Yuh hypothesized that the presence of an empty sella in conjunction with other imaging signs suggests a diagnosis of IIH when venous thrombosis, tumor, or infection is excluded, regardless of the limited specificity [12]. Other IIH imaging signs reported in previous studies [26,13,24,17,23] were more prevalent in the PT cohort than in control subjects, including a flattened posterior sclera, vertical tortuosity of the optic nerve, protrusion of the optic nerve, transverse sinus stenosis, and ONS distension. According to Maralani [14], a flattened posterior sclera strongly suggests a diagnosis of IIH (specificity 100 %; sensitivity 53.5 %).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Yuh hypothesized that the presence of an empty sella in conjunction with other imaging signs suggests a diagnosis of IIH when venous thrombosis, tumor, or infection is excluded, regardless of the limited specificity [12]. Other IIH imaging signs reported in previous studies [26,13,24,17,23] were more prevalent in the PT cohort than in control subjects, including a flattened posterior sclera, vertical tortuosity of the optic nerve, protrusion of the optic nerve, transverse sinus stenosis, and ONS distension. According to Maralani [14], a flattened posterior sclera strongly suggests a diagnosis of IIH (specificity 100 %; sensitivity 53.5 %).…”
Section: Discussionmentioning
confidence: 97%
“…Each image was evaluated for the following neuroimaging features, previously reported as imaging signs of IIH (Fig. 2): (1) flattening of the posterior sclera and the posterior aspect of the optic globe relative to the normal curvature of the globe, as observed on the axial T1-weighted images [23,17]; (2) vertical tortuosity of the orbital optic nerve, indicated by a redundant and S-shaped appearance on sagittal views [14,18]; (3) protrusion of the optic nerve head, straightening of the normally outwardly convex sclera, or concavity of the sclera towards the globe at the optic nerve attachment [14,24,17]; (4) empty sella, indicated by the pituitary gland filling less than 50 % of the sellar volume [23]; and (5) transverse sinus stenosis, the smallest diameter of transverse sinus was less than 50 % of the largest diameter. Morphometric analysis for IIHassociated features was performed [13,15,25,23,14,26,27], including the pituitary gland height, pituitary grade, ONS diameter, maximum width of the third ventricle, maximum width of the fourth ventricle, and lateral ventricle size (maximum and minimum widths of the anterior horns; Fig.…”
Section: Image Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…pp-BM as imaged by OCT serves as a surrogate for the flattening of the entire globe because of a pressure gradient involving ICP, and our analysis assumes that other factors affecting pp-BM shape such as changes in choroidal thickness altering the displacement of BM and sclera are negligible. This assumption is supported by the similarity of qualitative observations regarding ICP associations with globe shape based on pp-BM (OCT) 6 and peripapillary-sclera (magnetic resonance imaging) 3 and the likelihood that changes in choroidal thickness would diffusely alter the sclera-BM relationship to cause an offset rather than cause changes exclusively adjacent to the optic nerve as this and other globe-flattening studies have shown.…”
Section: Discussionmentioning
confidence: 56%
“…Unlike papilledema, this cannot be viewed on the ophthalmoscopic exam, although it can be readily appreciated using cross-sectional imaging such as magnetic resonance imaging, 3 where flattening is visualized as a change in the spherical contour of the globe or optical coherence tomography (OCT), 4 where flattening is seen as a less convex or even concave shape of the peripapillary Bruch's membrane (pp-BM) relative to the vitreous cavity. Previous studies have shown that globe contour and BM shape are different in patients with high ICP versus patients with normal ICP, 3,5 and in patients with high ICP who undergo medical or surgical treatment to lower ICP, there is a return of shape toward normal within 2 to 3 weeks. 5 The mechanism of this shape change has not been elucidated, but it is postulated that it is the result of the mechanical effect of increased fluid pressure in the optic nerve sheath.…”
mentioning
confidence: 99%